The chase - Cussler, Clive (Camberwell, Victoria Michael Joseph, 2007)
Cussler's latest adventure involves the hulk of a steam locomotive that comes to the surface of a lake in Montana in 1950. It contains the bodies of three men who died 44 years before. Flash back to 1906 and a two-year crime spree out west. There's a series of bank robberies by an evil person who murders any witnesses. The government brings in a detective to solve the case, but soon the hunter becomes the hunted. As always, Cussler ties everything together in the end
1
Keywords: Bank robberies -- Fiction; Bank robberies